Neocolonialism and Local Values: How Indigenous Peoples Preserve Their Cultural Identities in a Global Age - Syafitri, Musdalifah (Professorline, 2024)
Neocolonialism is a form of economic, political and cultural domination of developing countries in developing countries without direct colonization. This article shows how neo-colonialism affects the lives of indigenous peoples whose local values ​​differ from global values. This article also describes how indigenous peoples maintain their cultural identity through resistance, adaptation and transformation strategies. This article uses a qualitative approach to the case study method. Data were collected through in-depth interviews, participant observations and document analysis. The research results show that indigenous peoples face various challenges and pressures from neo-colonialism, such as exclusion, discrimination, exploitation and assimilation. However, indigenous peoples also have the strength and wisdom to preserve their local values, such as solidarity, cooperation, harmony and sustainability. This article advocates giving indigenous peoples the space and rights to decide their destiny according to local values.